PERAWATAN ORTODONTI DENGAN MENGGUNAKAN SISTEM DAMON: ORTHODONTIC TREATMENT WITH DAMON SYSTEM - Wilna Maiyestinoval; Nazruddin; Erliera (TALENTA, 2011)
Self- ligating bracket systems are currently one of the famous topics in orthodontics. There are many of these systems i n the market. However, the Damon bracket system is mostly the best known and widely used. The Damon system is a passive self- ligati ng method in correcting malocclusions. The Damon bracket system does not require o- rings to hold the wire in place, the Damon system uses small sliding doors. The absence of using o- rings, the wire freely slides through the slot without friction, which necessitates new mechanics to complete the treatment faster and more optimal. In conclusion, treatment procedures with Damon system become simpler and faster compared to conventional brackets.